Chronic myeloid leukaemia and tyrosine kinase inhibitor therapy: assessment and management of cardiovascular risk factors. (31st January 2018) - Ross, David M.; Arthur, Chris; Burbury, Kate; Ko, Brian S.; Mills, Anthony K.; Shortt, Jake; Kostner, Karam
Abstract: Several BCR‐ABL1 tyrosine kinase inhibitors (TKIs) are approved for the first‐line treatment of chronic phase chronic myeloid leukaemia (CML). Disease control is achieved in the vast majority of patients and disease‐specific survival is excellent. Consequently, there is now emphasis on managing comorbidities and minimising treatment‐related toxicity. Second‐generation TKIs have cardiovascular risks that are greater than with imatinib treatment, but these risks must be balanced against the superior CML responses encountered with more potent TKIs. Cardiovascular risk should be assessed at baseline using a locally validated model based on the Framingham risk equation. Clinicians involved in the care of CML patients should be aware of the vascular complications of TKIs and manage cardiovascular risk factors early to mitigate treatment‐related risks. Reversible risk factors, such as dyslipidaemia, smoking, diabetes and hypertension, should be addressed. We summarise the available data on cardiovascular complications in CML patients treated with TKIs. Using the latest evidence and collective expert opinion, we provide practical advice for clinicians to assess, stratify and manage cardiovascular risk in people with CML receiving TKI therapy.